Justiça e disciplina : análise das práticas de controle institucional na Polícia Militar do estado de Sergipe (2001-2009) - Lima, Elvoclebio de Araújo (2010)
This study entitled "Justice and Discipline: Analysis of Institutional Control Practices in the Military Police of the State of Sergipe (2001-2009)" aims to examine the practices of institutional control and consequent restatements in disciplinary power in the period between 2001 to 2009, whereas these restatements reflect the search for elements reaffirmation of the effective exercise of power practiced within the hierarchical relationships-disciplinary. The reaffirmation of the domain of military authority, at any given time, assumed the aspect of a discourse oriented legal grounds to punish the act. The emergence of "new" procedures of accountability and culpability of the offender characterized the concern of military authority regarding maintenance of disciplinary content of hierarchical relationships. Using the documentary research, based on publications made in bulletin Overall, the analysis focused practices of empowerment appealed also to speak of the subject, trying, through discourse agents, make an overview of the concepts and representations concerning discipline and justice. In the scenario presented by institutional PMSE during the period in question, the transgression appears as one of the categories of the phenomenon of misconduct, thoughtful, often from two angles: the relations disciplinary transgression in this case was taken as a result of disobedience, the penalty being applied in the form of educational intervention, the background takes misconduct in higher degree, considering it as a serious deviation from the behavior, distanced professional ethics and responsible for military cause problems, eg, the police violence. During selected view which tried to design transgression existing in the institution and how it justifies the notion of "disciplining" and criminal liability and administrative officer practiced by the military authority. Amid the data relating to punishments and disciplinary procedures and judicial perceive problems as the transparency of procedures, preventing often the external observation of practice and investigation of allegations of criminal offenses. There was also a more effective coercive apparatus for the application of disciplinary punishments related to the discipline of the troops, however, this efficacy contrasts with the results of established procedures for verification of complaints of abuse of power committed by military police. One of the factors affecting the poor visibility of the route taken by the procedure is precisely the institutional design given by the militarism that treats the misconduct as something that concerns the military world, undermining a broader understanding of the effects of violence and transgression committed by police.